Virtual Reality Game Design for the Reduction of Chronic Pain Intensity in Clinical Settings - Choo, Amber (Simon Fraser University, 2015)
Virtual reality applications have been shown to reduce discomfort and pain in acute pain patient demographics including dental patients, chemotherapy patients and burn patients. Currently little research literature exists on the effectiveness of virtual reality applications for chronic pain patients, who suffer from longer-term persistent pain experiences. This thesis outlines the testing of virtual environments designed to distract chronic pain patients from their embodied pain experiences. Their designs are influenced by contemporary game design theory, cognitive psychology and immersion frameworks. In a randomized crossover clinical study, twenty chronic pain patients spent ten minutes in Cryoslide, a virtual environment, using a head-mounted display, and ten minutes in a control condition. Cryoslide significantly reduced perceived pain intensity in chronic pain patients in the experimental condition. This shows that Cryoslide can be effectively used as an analgesic activity by chronic pain patients to lessen chronic pain intensity in short-term durations. The immersive design of Cryoslide contributes to the pain research community by directly addressing the lack of virtual reality research for chronic pain patients in the research literature. The results of Cryoslide's clinical testing encourage future research inquiries into virtual reality applications designed for chronic pain patients with kinesiophobia, and virtual reality applications on mobile devices for at-home patient use.
Keywords: Riecke; Riecke_2015; Riecke_supervised_thesis; SIAT; amber-choo; bernhard-riecke; chris-shaw; diane-gromala; supervisedThesis; thesis